Pengaruh Dukungan Keluarga, Self Efficacy dan Resiliensi Terhadap Minat Berwirausaha Generasi Z di Kota Denpasar Bali - Sri Pradnyanita, Ni Komang Ayu; Lasmi, Ni Wayan (MES Bogor, 2026)
This study aims to analyze the influence of family support, self-efficacy, and resilience on the entrepreneurial interest of Generation Z in Denpasar City, which, despite having significant potential as well as access to technology and a developing creative ecosystem, still faces low entrepreneurial interest, limited skills, experience, and environmental support. The study employed purposive sampling involving 100 Generation Z respondents across four districts in Denpasar City, collecting primary data through questionnaires and secondary data from various sources to obtain a comprehensive overview of factors affecting entrepreneurial interest. The results of this study are: (1) Influence of Family Support, Self-Efficacy, and Resilience on Entrepreneurial Interest: simultaneously, family support, self-efficacy, and resilience have a positive and significant effect on the entrepreneurial interest of Generation Z in Denpasar City with a contribution of 52.4%; (2) Influence of Family Support on Entrepreneurial Interest: family support has a positive and significant effect on the entrepreneurial interest of Generation Z in Denpasar City with a contribution of 45.5%, as motivation, guidance, and trust from family create a conducive environment for entrepreneurship; (3) Influence of Self-Efficacy on Entrepreneurial Interest: self-efficacy has a positive and significant effect on the entrepreneurial interest of Generation Z in Denpasar City by 24.8%, as self-confidence enhances courage, readiness, and the ability to seize business opportunities; and (4) Influence of Resilience on Entrepreneurial Interest: resilience has a positive and significant effect on the entrepreneurial interest of Generation Z by 25.8%, as the ability to recover from failure and face pressure increases motivation and perseverance in starting a business.